Service Strategy of PT. Zakiah Dina Tayyibah on Prospective Umrah and Pilgrims: Analysis of Islamic Business Ethics - Perawati, Eka; Aminah, St (Al-Iftah: Journal of Islamic studies and society, 2020)
One of the Hajj and Umrah travel that develops in Parepare City is PT. Zakiah Dina Tayyibah, which has been operating since 2008 and in 2014, has obtained a permit for organizing Umrah Worship Tourists (PPIU) from the Ministry of Religion. This Study discusses the form of guidance, the form of service, and the form of protection of the umrah pilgrims at PT. Zakiah In Tayyibah. This type of research is an empirical study using descriptive qualitative. The primary data sources in this study are the Directors, employees and members of PT. Zakiah In Tayyibah. While secondary data are scientific books and journals. The results of this study are the form of coaching conducted by PT. Zakiah Dina Tayyibah is good enough, that is by giving manasik guidance to prospective pilgrims who will depart; the form of service of PT. Zakiah Dina Tayyibah is good enough by paying attention to reliability, responsiveness, assurance, empathy and tangible to the prospective Jamaat who will go to worship to the holy land; the form of protection provided by PT. Zakiah Dina Tayyibah to the congregation is to provide insurance in the form of cooperation with the insurance company ADIRA. In the application of the three leading sectors above at PT. Zakiah Dina Tayyibah has fulfilled the elements of Islamic business ethics namely justice, honesty, trustworthiness and transparency.